Harnessing The Potential Of Storytelling On Social Media: A Game-Changer For Halal Tourism Marketing Strategies - Harry Setiawan; Nur Afifah; Mustaruddin, Mustaruddin (SEAN Institute, 2024)
The rapid growth of the halal tourism market presents significant opportunities for destinations and service providers. However, to effectively capitalize on this potential, it is crucial to understand the factors influencing Muslim tourists' experiences and revisit intentions. This study aims to investigate the role of storytelling on social media as a moderating variable in the relationship between Muslim tourists' emotional experiences and their intention to revisit halal tourism destinations. A quantitative approach and structural equation modeling were employed to examine the impact of halal destination attributes and halal-friendly services on emotional experiences, as well as the moderating effect of storytelling on social media on the relationship between emotional experiences and revisit intentions. The analysis results demonstrate that halal destination attributes and halal-friendly services significantly influence Muslim tourists' emotional experiences. Furthermore, storytelling on social media significantly moderates the relationship between emotional experiences and revisit intentions, strengthening the impact of emotional experiences on post-visit behavioral intentions. These findings contribute to the advancement of tourism marketing and consumer behavior theories while providing practical implications for the halal tourism industry in designing effective marketing strategies through social media storytelling.